The Pharmacokinetic and Absolute Bioavailability of Cyclosporine (Atopica for Cats®) in Cats - Jingyuan Kong; Yuxin Yang; Yu Liu; Yuying Cao; Jicheng Qiu; Pan Sun; Xingyuan Cao (Veterinary Sciences, 2023)
This study aimed to evaluate the absolute bioavailability of cyclosporine in cats by investigating the pharmacokinetic profile after intravenous and oral administration, respectively. Twenty-four clinically healthy cats were enrolled in this study and randomly divided into four groups, namely the intravenous group (3 mg/kg), low oral group (3.5 mg/kg), medium oral group (7 mg/kg), and high oral group (14 mg/kg). Whole blood was obtained at the scheduled time points after a single dose administration and cyclosporine was determined using ultra-performance liquid chromatography–tandem mass spectrometry technology (UPLC-MS/MS). Pharmacokinetic parameters were calculated using the WinNonlin 8.3.4 software via compartmental and non-compartmental models. As a result, the bioavailability values for the low, medium, and high oral groups were 14.64%, 36.98%, and 13.53%, respectively. The nonlinear pharmacokinetic profile was observed in the range from 3.5 mg/kg to 14 mg/kg in cats following oral administration. Whole blood concentrations taken 4 h after oral administration were better correlated with the area under the blood concentration–time curve AUC0–24 with a high regression coefficient (R2 = 0.896). This concentration would be a greater predictor in the following therapeutic drug monitoring. No adverse effect was observed in the whole study process.